Identification of UAV static aerodynamic characteristics in the water tunnel balance research - Daniel Lichoń; Anna Mikołajczyk; Łukasz Kiszkowiak; Tomasz Łącki (Advances in Mechanical and Materials Engineering, 2016)
This work presents the identification of static aerodynamic characteristics in the water tunnel experiments. The tested object was a scale model of unmanned aerial vehicle (UAV) target drone OCP-Jet. The research was performed in the water tunnel Rolling Hills Research Corporation model no. 2436, Military University of Technology, Warsaw. Water tunnel experiments allow to perform static and dynamic balance measurements, dye flow visualizations and PIV flow field measurements. The advantage of the use of the water tunnel are relatively inexpensive researches and the possibility to use small models manufactured with 3D printing technology. However, testing the flying objects in the water medium has limitations due to difficulties in satisfying the flow similarity criteria. In this paper the researches were focused on identification of the static aerodynamic characteristics with the use of balance measurements. The forces and moments characteristics were performed. The experimental results were compared with full scale aircraft characteristics, calculated with analytical methods and vortex lattice method.